Efek Mediasi Perilaku Keuangan Pada Pengaruh Faktor Demografi, Literasi Keuangan dan Efikasi Terhadap Keputusan Investasi - Khatimah, Husnul; Ampauleng, Ampauleng; Sohilauw, Muhammad Irfai (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Investors’ efforts to minimise losses and gain profits are a manifestation of their accuracy and accuracy in making the right investment decisions. This study uses a positivism approach using 100 undergraduate students at the Makassar Bongaya College of Economics as a sample. Data analysis was carried out using structural equation models through Partial Least Square using the SmartPls 3.0 program. The results of testing the outer model and inner model show that all data meet the test requirements so that evidence is obtained that demographic factors and efficacy affect financial behaviour, efficacy and financial behaviour affect investment decisions, demographic factors and literacy have no effect on investment decisions, financial literacy has no effect on financial behaviour. Indirect research results show that demographic factors and efficacy affect investment decisions with financial behaviour as intervening, on the other hand, evidence is found that financial literacy has no effect on investment decisions with financial behaviour as intervening.